B cell receptors in TCL1 transgenic mice resemble those of aggressive, treatment-resistant human chronic lymphocytic leukemia - Yan, Xiao-jie; Albesiano, Emilia; Zanesi, Nicola; Yancopoulos, Sophia; Sawyer, Alan; Romano, Egidio; Petlickovski, Aleksandar; Efremov, Dimitar G; Croce, Carlo M; Chiorazzi, Nicholas (Proceedings of the National Academy of Sciences, 2006)
B cell chronic lymphocytic leukemia (B-CLL) is a clonal overgrowth of CD5(+) B lymphocytes. In this disease, the B cell antigen receptor (BCR) is intimately linked to disease severity, because patients with BCRs, comprised of unmutated V(H) genes, follow a much more aggressive course. This and related observations suggest that B-CLL derives from a B cell subset comprised of restricted BCR structural diversity and that antigen-selection and drive are major factors promoting the disease. Nevertheless, the initiating event(s) that lead to the development of B-CLL are still unclear, in part because of the lack of an animal model that spontaneously evolves the molecular abnormalities that occur in the human disease. Because overexpression of the TCL1 gene in murine B cells leads to a CD5(+) B cell lymphoproliferative disorder with many of the features of human B-CLL, we studied leukemias emerging in these mice to examine the extent to which their BCRs resemble those in B-CLL. Our data indicate that the immunoglobulin heavy and light chain rearrangements in TCL1 mice display minimal levels of somatic mutations and exhibit several molecular features found in the human disease. Like human B-CLL, TCL1 leukemic rearrangements from different mice can be very similar structurally and closely resemble autoantibodies and antibodies reactive with microbial antigens. Antigen-binding analyses confirm that selected TCL1 clones react with glycerophospholipid, lipoprotein, and polysaccharides that can be autoantigens and be expressed by microbes. This (auto)antigen-driven mouse model reliably captures the BCR characteristics of aggressive, treatment-resistant human B-CLL.